Beliefs of general classroom and music specialist teachers in Hungarian primary schools regarding the development of musical abilities in children - Asztalos Andrea (2022)
One of the most important issues in music education is the development of children’s musical abilities, which are in turn impacted by teachers’ beliefs. The purpose of this study was to investigate the beliefs of general classroom and music specialist teachers in Hungary about the development of the musical abilities of children. A total of 176 general classroom teachers and 272 music specialist teachers participated in the research process. Data were collected using an online questionnaire method. SPSS was used to process data using quantitative methods. The researcher used descriptive statistical methods (frequencies, means, standard deviations) for data analysis, and inferential statistics—independent samples t test, Pearson’s correlation, and factor analysis (Maximum Likelihood method, Oblimin rotation)—to examine differences and correlations between variables. The results indicated that teachers cognitively organize musical abilities differently from the Hungarian National Core Curriculum content. Moreover, the study observed several differences among the beliefs of general classroom and music specialist teachers regarding the level of development of musical abilities of primary school children. A significant correlation was noted between the teachers’ qualifications, practice, and length of instrumental learning, and their beliefs about developing musical abilities in children. One main educational implication emerged from the results was the importance of modification of beliefs for educating teachers in university courses, which poses a major problem because changing teachers’ beliefs is a complex process.
Keywords: Oktatástudomány